Free-living nematodes of the genus Syringolaimus de Man, 1888 (Nematoda, Enoplida, Ironidae) from the Angola Basin, South-East Atlantic Abyss - Tchesunov, Alexei V. (Zootaxa, 2017)
Three nematode species of the genus Syringolaimus (Enoplida, Ironidae) were found in the Angola Basin (south-east Atlantic Ocean) at depths of almost 5500 m. One of them is described as new for science and the other two were initially recorded from the deep sea off the Brazilian coast and are redescribed here. Syringolaimus elegans sp. n. differs from all other species of Syringolaimus by a slimmer body (a=99 vs. 30–73) and from all species except S. ingens (nom. nud.) by its greater body length (2718 μm vs. 760–1750 μm), longer buccal cavity (79 μm vs. 28–58 μm), and longer terminal pharyngeal bulb (70 μm vs. 53 μm). All the Syringolaimus species together make up from 0.75 to 2.82% of all nematode individuals from all samples. Diagnoses of Syringolaimus annae Lima et al., 2009 and S. smolae Lima et al., 2009 are updated. An annotated list of Syringolaimus species is provided; the species annae, elegans, filicaudatus, loofi, magdae, renaudae, smolae, striatocaudatus and taniae are considered as valid, while brevicaudatus, caspersi, lichenii, marisalbi, smarigdus and venustus as species inquirendae, and gladiatus, ingens, nitidus and venustus as nomina nuda. Diagnostic characters and problems of species identification are discussed.